2009
DOI: 10.1074/jbc.c900009200
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Cavernous Malformation 2 Protein Promotes Smad Ubiquitin Regulatory Factor 1-mediated RhoA Degradation in Endothelial Cells

Abstract: Mutation of CCM2 predisposes individuals to cerebral cavernous malformations, vascular abnormalities that cause seizures and hemorrhagic stroke. CCM2 has been proposed to regulate the activity of RhoA for maintenance of vascular integrity. Herein, we define a novel mechanism where the CCM2 phosphotyrosine binding (PTB) domain binds the ubiquitin ligase (E3) Smurf1, controlling RhoA degradation. Brain endothelial cells with knockdown of CCM2 have increased RhoA protein and display impaired directed cell migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 14 publications
2
93
2
Order By: Relevance
“…In addition to its ability to ubiquitylate talin (Huang et al, 2009), Smurf1 was a good candidate for ICAP-1 monoubiquitylation because Smurf1 associates with the cerebral cavernous malformations (CCM) complex (Crose et al, 2009), which interacts with ICAP-1 (Hilder et al, 2007). Smurf1 also possesses an NPxY motif that might be able to interact with ICAP-1 phosphotyrosine-binding (PTB) domain.…”
Section: Smurf1 As a Node To Control Focal Adhesion Dynamics And Cellmentioning
confidence: 99%
“…In addition to its ability to ubiquitylate talin (Huang et al, 2009), Smurf1 was a good candidate for ICAP-1 monoubiquitylation because Smurf1 associates with the cerebral cavernous malformations (CCM) complex (Crose et al, 2009), which interacts with ICAP-1 (Hilder et al, 2007). Smurf1 also possesses an NPxY motif that might be able to interact with ICAP-1 phosphotyrosine-binding (PTB) domain.…”
Section: Smurf1 As a Node To Control Focal Adhesion Dynamics And Cellmentioning
confidence: 99%
“…17 Although this proposal remains speculative, one could imagine that the endothelium in CCM lesions harbors certain unique properties because the lesions have been exposed to this abnormal, yet undefined, microenvironment. Within this context and considering that the functional study of CCM genes in culture has been performed exclusively in cell lines 3,5,6,14 or in commercially purchased normal ECs (HUVECs and HBMECs), 6,25 silencing CCM genes in CCM-ECs established in the present work may simulate some aspects of the diseased endothelium in the CCM lesions, and thus may serve as a unique and valuable model for investigating the function of CCM genes in the pathogenesis of CCMs.…”
Section: Discussionmentioning
confidence: 99%
“…8,24 The role of CCM2 in maintenance of vascular integrity has been proposed through regulating the activity of Ras homolog gene family member A. The mechanism of this regulation has been recently addressed by Crose et al 6 The CCM3 gene is suggested to be involved in apoptosis 5,14 and tumor signaling. 14 We found that loss of CCM3 led to a significant resistance of all 3 tested types of ECs to apoptotic stimuli (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The first indication that RhoA dysregulation might contribute to CCM pathology came from the observation of increased stress fiber formation (a sign of activated RhoA) after RNAinterference-mediated knockdown of any of the CCM proteins (Crose et al, 2009;Glading et al, 2007;Stockton et al, 2010;Whitehead et al, 2009;Zheng et al, 2010). Consistent with this, activated (GTP-bound) RhoA is increased in KRIT1-, CCM2-or PDCD10-deficient endothelial cells.…”
Section: The Role Of Ccm Proteins In Rhoa-rock Signalingmentioning
confidence: 86%
“…In addition, CCM2 appears to direct the degradation of RhoA through a CCM2 PTB-domain-mediated interaction with the E3 ubiquitin ligase Smad ubiquitin regulatory factor 1 (SMURF1) (Crose et al, 2009). Notably, loss of CCM2 leads to increases in RhoA, but not of other SMURF1 substrates, suggesting that CCM2 might selectively promote SMURF1-mediated RhoA degradation.…”
Section: The Role Of Ccm Proteins In Rhoa-rock Signalingmentioning
confidence: 99%